Konsep perpaduan dalam masyarakat Malaysia madani menurut hadis terpilih daripada hadis 40 Imam Nawawi - Nurul Hidayah Arom; Muhammad Nur Farhan Zamziba; Siti Hanisah Sabri; Nor Fatin Syuhaidah Nayan (Universiti Sains Islam Malaysia, 2025)
The Unity Government formed by Prime Minister Dato’ Seri Anwar Ibrahim after Malaysia’s 15th General Election introduced the Malaysia MADANI concept as a framework for national development based on unity and universal values. This concept promotes a dynamic, inclusive, and compassionate society built on trust, respect, and moral values. This study aims to identify the characteristics of a MADANI society through selected hadiths from Imam al-Nawawi’s Forty Hadiths, as part of an initiative to develop an educational module for hadith appreciation in Malaysia’s education system. This research uses a qualitative library-based method, analyzing the Forty Hadiths through content analysis supported by classical and contemporary scholarly interpretations. The study focuses on unity-related values found in selected hadiths. The findings show that several hadiths reflect key principles in line with Malaysia MADANI’s core components: Mulia (Morality), Agama (Religion), Daim (Sustainability), Adil (Justice), Nasihat (Advisory), and Ikhlas (Sincerity). These values help strengthen unity in a multi-ethnic and harmonious society. This study provides a foundation for developing hadith-based educational content and supports the goal of national unity through an inclusive Islamic approach relevant to modern society.